Clinical practice recommendations for quality of life assessment in patients with gynecological cancer - Leppert, Wojciech; Gottwald, Leszek; Forycka, Maria (Menopause Review/Przegląd Menopauzalny, 2015)
Quality of life (QoL) is a multidimensional concept regarding self-assessment of patients’ situation. Quality of life has not been clearly defined up to date, although it is clear that it is a subjective self-assessment that to a significant extent is determined by individual needs, beliefs, values, attitudes, which are changing with time. Health-related QoL comprises basic dimensions such as patients’ performance status, physical, emotional, and social functioning, symptoms of the disease and adverse effects of treatment, spiritual (God and existential) and other dimensions. In women, the ovary, cervical, corpus uterus, vagina and vulva cancers deteriorate QoL by disease progression and consequences of treatment, also in cancer survivors. Common symptoms include the genito-urinary system, the lower gastrointestinal tract and peripheral neuropathies induced by chemotherapy. In young women, QoL is impaired by infertility, sexual problems and menopause symptoms. An overview of QoL questionnaires used in oncology with special regard to patients with gynecological tumors was conducted. A screening tool for psychological state assessment of oncology patients (distress thermometer), the Edmonton Symptom Assessment System (ESAS) and modular approach of QoL assessment recommended by the EORTC (European Organization for the Research and Treatment of Cancer) were presented. Practical guidelines were proposed to assess appropriately QoL in patients with gynecological cancers who stay at in-patient gynecology units and those treated at home and in an ambulatory care setting.